2006
DOI: 10.1016/j.virol.2005.11.042
|View full text |Cite
|
Sign up to set email alerts
|

SARS coronavirus nucleocapsid immunodominant T-cell epitope cluster is common to both exogenous recombinant and endogenous DNA-encoded immunogens

Abstract: Correspondence between the T-cell epitope responses of vaccine immunogens and those of pathogen antigens is critical to vaccine efficacy. In the present study, we analyzed the spectrum of immune responses of mice to three different forms of the SARS coronavirus nucleocapsid (N): (1) exogenous recombinant protein (N-GST) with Freund's adjuvant; (2) DNA encoding unmodified N as an endogenous cytoplasmic protein (pN); and (3) DNA encoding N as a LAMP-1 chimera targeted to the lysosomal MHC II compartment (p-LAMP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 82 publications
5
58
0
Order By: Relevance
“…In an effort to develop an optimal DNA vaccine against rabies virus, this study was aimed at evaluating the immune enhancement potential of different antigen targeting strategies to selectively improve responses mediated by CD8 + and CD4 + T lymphocytes and by antibodies, induced after intramuscular immunization with DNA plasmids. Addition of target sequences like TPA, LAMP-1, UQ have been employed for vaccination against various pathogens including SARS coronavirus [35]; Dengue virus [36]; Orthopox virus Fig. 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to develop an optimal DNA vaccine against rabies virus, this study was aimed at evaluating the immune enhancement potential of different antigen targeting strategies to selectively improve responses mediated by CD8 + and CD4 + T lymphocytes and by antibodies, induced after intramuscular immunization with DNA plasmids. Addition of target sequences like TPA, LAMP-1, UQ have been employed for vaccination against various pathogens including SARS coronavirus [35]; Dengue virus [36]; Orthopox virus Fig. 7.…”
Section: Discussionmentioning
confidence: 99%
“…They inferred that TM domain is critical for proper folding of protein otherwise the critical epitopes may get disrupted [30]. Gupta et al also reported that DNA vaccine encoding rabies virus glycoprotein lacking transmembrane domain though enhances antibody response but does not confer protection [35]. Therefore, we retained the TM domain in our DNA vaccine constructs and utilized full gene for targeting strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The luminal domain of LAMP is then integrated into the lysosome. [10][11][12][13][14][15][16][17] Consequently, one strategy commonly adopted by our group [18][19][20][21][22][23][24][25] is to insert the target DNA into LAMP as a LAMP/ antigen chimera. In addition, many other laboratories have reported that LAMP targeting could greatly enhance the immune response against a number of antigens.…”
Section: Introductionmentioning
confidence: 99%
“…promiscuous T-cell epitopes may be localized in clusters, as reported in studies of HIV-1 [29][30][31][32] and the outer membrane of Chlamydia trachomatis [33], among others [34,35]. The clusters are also ideal for developing epitopebased vaccines because they contain multiple promiscuous epitopes.…”
Section: Immunological Hotspots-putativementioning
confidence: 92%